Management practice of medical waste disposal during the COVID-19 epidemic (新型冠状病毒肺炎疫情防控期间医疗垃圾处理的管理实践) - ZHU Xiaodan (朱晓丹); ZHANG Huilan (张慧兰); YOU Jianping (游建平); YANG Sha (杨莎) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the practice in the management of medical waste disposal during the COVID-19 epidemic. Plan and targeted strategies were made based on the considerations regarding the layout of medical waste disposal, transport process, the main points of transport routes in fever clinics, isolation (under observation) wards and laboratory in the hospital. This paper is dedicated to provide reference for other medical institutes to establish and practice a timely, orderly, efficient and harmless disposal of medical waste when dealing with severe infectious diseases. (本文总结医院在新型冠状病毒肺炎疫情期间医疗垃圾处理的管理实践经验, 包括发热门诊、隔离(留观)病房和实验室产生的医疗垃圾的存储布局、转运流程、转运路线及处理要点等, 以期为其他医疗机构在应对烈性传染病时确保医疗垃圾得到及时、有序、高效、无害化处置提供借鉴。)